2013
DOI: 10.1371/journal.pbio.1001524
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Role for Human Nup98 in Altering Chromatin Structure and Promoting Epigenetic Transcriptional Memory

Abstract: In yeast and humans, interaction of a nuclear pore protein with promoters alters chromatin structure and allows RNA polymerase II to bind, poising them for faster reactivation for several generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
298
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(327 citation statements)
references
References 90 publications
(163 reference statements)
20
298
0
Order By: Relevance
“…Using two independent assays, we found no defect in nuclear export or import on depletion of Nup98 or several other nuclear pore proteins. This finding is consistent with two recent studies that found no role for Nup98 in nuclear transport when Nup98 was compromised (22,28). In addition, using single-molecule RNA FISH, we detected no defect in nuclear export of B52 or CG9008 mRNA on depletion of Nup98.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Using two independent assays, we found no defect in nuclear export or import on depletion of Nup98 or several other nuclear pore proteins. This finding is consistent with two recent studies that found no role for Nup98 in nuclear transport when Nup98 was compromised (22,28). In addition, using single-molecule RNA FISH, we detected no defect in nuclear export of B52 or CG9008 mRNA on depletion of Nup98.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that Nup98 localizes predominantly to the nuclear pore complex, but has an additional population in the nucleoplasm and can exhibit altered nuclear distribution in response to some stimuli, such as developmental signaling or IFN-γ (19,20,22,34). In our system, we found that Nup98 levels are increased on viral infection (Fig.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations